1996
DOI: 10.1200/jco.1996.14.6.1943
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous regression of lymphoproliferative disorders in patients treated with methotrexate for rheumatoid arthritis and other rheumatic diseases.

Abstract: MTX withdrawal and observation for a short period should be considered in the initial management of patients who develop LPD while on MTX therapy. Responses were consistently observed, but not limited to patients in whom EBV was detected by ISHS or PCR. Further studies are required to confirm these findings and to evaluate the role for EBV in LPD that occur in patients receiving MTX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
235
2
7

Year Published

1997
1997
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 352 publications
(252 citation statements)
references
References 30 publications
8
235
2
7
Order By: Relevance
“…In RA patients treated with methotrexate, studies have shown varying results. EBV has been detected in 16-44% of lymphomas (14,15,26), and, as in the present study, a role for EBV in lymphoma development cannot be ruled out.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In RA patients treated with methotrexate, studies have shown varying results. EBV has been detected in 16-44% of lymphomas (14,15,26), and, as in the present study, a role for EBV in lymphoma development cannot be ruled out.…”
Section: Discussionsupporting
confidence: 53%
“…The reason for this association is still incompletely understood, but immunosuppressive therapy in RA (6)(7)(8)(9)(10) as well as Epstein-Barr virus (EBV) infection may play a role in the development of these lymphomas (11)(12)(13)(14)(15). Additionally, both we (16) and others (17) have reported that high RA disease activity in itself may be associated with an increased lymphoma risk.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, spontaneous regression was possible after the withdrawal of MTX in 88.9% of MTX-LPD patients (4). Therefore, EBV infection appears to contribute to RA-MTX-LPD onset (19).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, LPD developed by immunodeficient patients treated with MTX is defined as MTXassociated LPD (MTX-LPD) in the 2008 World Health Organization Classification of Tumours of Haematopoietic and Lymphoid Tissues (3). MTX-LPD has the following characteristics: the Epstein-Barr virus (EBV) genome is present in lymphoma cells, and MTX withdrawal can potentially result in spontaneous regression of the lymphoma (4,5). However, the risk factors concerning MTX-LPD onset have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%